Trends of the Lithuanian Intelligentsia in the First Half of the 19th Century - Lukšienė, Meilė (Problemos, 1972)
The initial point of the article is the poem by A. Baranauskas “Poet’s Talks with Lithuania” (1859) where three tendencies of the cultural and national movement in Lithuania are marked out. Referring to ample archive material the author states that the poet had reason enough to single out three trends in the cultural life of Lithuania in the mid one 19th century. Actually, they were two – the progressive and the reactionary. Besides, the author raises the question of the necessity to emphasize the democratic origin of intelligentsia and some other related questions.